2022
DOI: 10.3390/jcm11030600
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Cutaneous Manifestations in COVID-19 Patients during the Pandemic

Abstract: After the beginning of the SARS-CoV-2 pandemic, our dermatology department created a multidisciplinary unit to manage patients with cutaneous manifestations associated with COVID-19. With the objective of identifying skin lesions in patients with suspected COVID-19 and evaluating possible associations with systemic involvement, other infectious agents and coagulation disorders, we carried out a prospective observational study that included all patients that attended our COVID-19 dermatology clinic with a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Though all of the studies in this review were observational study by nature with heterogenous data, 11 of them are retrospective study and the rest 8 of them are prospective studies [ [11] , [12] , [13] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] . Heterogeneity was observed in terms of population, study design (both prospective and retrospective), exposure reporting, and outcome reporting.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Though all of the studies in this review were observational study by nature with heterogenous data, 11 of them are retrospective study and the rest 8 of them are prospective studies [ [11] , [12] , [13] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] . Heterogeneity was observed in terms of population, study design (both prospective and retrospective), exposure reporting, and outcome reporting.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 539 participants were included in this study. Studies were conducted in all six WHO regions and the highest 10 studies were from WHO EUR region [ 11 , 25 , [27] , [28] , [29] , [30] , [31] , [32] , 34 , 36 , 38 ]. Though various ethnicities were included, in this review no association was found between ethnicities and Herpesviridae co-infection or reactivation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations